Hierarchy‐guided neural network for species classification. Issue 3 (5th December 2021) - Elhamod, Mohannad; Diamond, Kelly M.; Maga, A. Murat; Bakis, Yasin; Bart, Henry L.; Mabee, Paula; Dahdul, Wasila; Leipzig, Jeremy; Greenberg, Jane; Avants, Brian; Karpatne, Anuj
Abstract: Species classification is an important task which is the foundation of industrial, commercial, ecological and scientific applications involving the study of species distributions, dynamics and evolution. While conventional approaches for this task use off‐the‐shelf machine learning (ML) methods such as existing Convolutional Neural Network (ConvNet) architectures, there is an opportunity to inform the ConvNet architecture using our knowledge of biological hierarchies among taxonomic classes. In this work, we propose a new approach for species classification termed hierarchy‐guided neural network (HGNN ), which infuses hierarchical taxonomic information into the neural network's training to guide the structure and relationships among the extracted features. We perform extensive experiments on an illustrative use‐case of classifying fish species to demonstrate that HGNN outperforms conventional ConvNet models in terms of classification accuracy, especially under scarce training data conditions. We also observe that HGNN shows better resilience to adversarial occlusions, when some of the most informative patch regions of the image are intentionally blocked and their effect on classification accuracy is studied.